2018
DOI: 10.5152/tud.2018.76702
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of contrast-enhanced voiding urosonography with voiding cystourethrography in pediatric vesicoureteral reflux

Abstract: ce-VUS is a good imaging modality when compared to voiding cystourethrography to assess pediatric vesicoureteral reflux, in view of its superior diagnostic performance, feasibility and radiation safety for children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In this retrospective study, patients with recurrent febrile UTIs or with first febrile UTIs, accompanied with abnormal findings on renal ultrasonography underwent ceVUS, regadless the sex, according to the current recommendations (16,(19)(20)(21). The study lasted 3 years (from March 2017 until the end of February 2020).…”
Section: Patients and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this retrospective study, patients with recurrent febrile UTIs or with first febrile UTIs, accompanied with abnormal findings on renal ultrasonography underwent ceVUS, regadless the sex, according to the current recommendations (16,(19)(20)(21). The study lasted 3 years (from March 2017 until the end of February 2020).…”
Section: Patients and Data Collectionmentioning
confidence: 99%
“…The new ceVUS procedure with second generation of UCA brought the new possibilities in the diagnostics of VUR and IRR, especially in the grading system in five grades. Some studies reported higher sensitivity of ceVUS compared with VCUG and comparable results with direct radionuclide cystography, regarding the VUR detection (16)(17)(18)(19)(20)(21)(22)(23). The aim of this study was to analyze the incidence of IRR among VURs diagnosed by Abbreviations: ceVUS, contrast-enhanced voiding urosonography; IRR, intrarenal reflux; UCA, ultrasound contrast agent; URU, ureterorenal unit; VUR, vesicoureteral reflux; VCUG, voidingcystourethrography.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of performing the examination directly at the patient’s bedside can also generate a relaxed atmosphere for the patient, which has a positive effect on the doctor-patient relationship, especially for small children. In terms of cost-effectiveness, ceVUS is also superior to VCUG [ 20 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its radiation-free nature, the ceVUS also offers high sensitivity and specificity in comparison to the VCUG, as well as a good diagnostic evaluation of the urethra, which makes ceVUS interesting in the diagnostic cascade for the exclusion or quantification of VUR [ 6 , 16 , 17 ]. Compared to VCUG, ceVUS shows excellent diagnostic sensitivity of up to 100% in detecting VUR [ 18 , 19 , 20 ]. In order to visualize and diagnose VUR, contrast medium is injected into the bladder via a urinary catheter.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 1010 children ages 15 days to 17.6 years evaluated with ceVUS, no serious adverse event occurred, and only a few minor events occurred, likely because of catheterization. 22 More recent prospective clinical trials in which the authors compared the diagnostic sensitivity of VCUG and ceVUS revealed comparable 23 or superior 24 diagnostic sensitivity of ceVUS in comparison with the conventional VCUG. The higher sensitivity of ceVUS in the detection of vesicoureteral reflux and the ability to conduct a detailed evaluation of the urethra have enabled ceVUS to replace VCUG.…”
Section: Figurementioning
confidence: 99%